Tindak tutur ilokusi dalam film pendek “Sodara Seng Sedarah” karya Geraldy Laimera: Kajian pragmatik - Opier, Uun Ushwatun Khasana; Sri Harini Ekowati; Miftahulkhairah Anwar (Franconesia, 2023)
This research aims to describe the types of illocutionary speech acts in the short film "Sodara Seng Sedarah". This research uses Searle's speech act theory, which categorizes illocutionary speech acts into five categories: assertive, directive, expressive, commissive, and declarative. The method used is descriptive qualitative. The data source of this research is the dialog or speech uttered by the characters in the short film "Sodara Seng Sedarah". The data collection technique uses free listening technique (SBLC) and note-taking technique. Data analysis in this study uses the pragmatic pairing method to identify language units based on the speech partner's response to the utterance. Data analysis will be described according to the problem in the form of words or sentences. The data presentation is organized according to the theory of illocutionary acts described by Searle. The results concluded that in the short film "Sodara Seng Sedarah" by Geraldy Laimera, there are four types of illocutionary speech acts that appear in conversations between characters, namely assertive, directive, expressive, and commissive. (1) the assertive type of illocution involves informing and suggesting speech. (2) the directive type of illocution includes pleading, advising, and commanding. (3) Expressive illocutionary type involves apologizing and thanking speech. (4) the commissive type of illocution is in the form of threatening speech. No declarative illocutionary speech acts are found in the dialog of the short film "Sodara Seng Sedara".